The Implementation of Jigsaw Strategy to Improve Students’ Active Participation in Learning of Tarjamah, Class of Grade 4 KMI at Third Campus of Darussalam Gontor Islamic Boarding School Academic Year: 1438-1439 H - Luthfi Muhyiddin; Hazrati Zharfa (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2018)
The Implementation of Jigsaw Strategy to Improve Students’ Active Participation in Learning of Tarjamah, Class of Grade 4 KMI at Third Campus of Darussalam Gontor Islamic Boarding School Academic Year: 1438-1439 H  Luthfi Muhyiddin, Hazrati Zharfaluthfimuhyiddin@unida.gontor.ac.id, hazratizharfa@gmail.comUniversity of Darussalam Gontor ABSTRACTDarussalam Gontor Islamic Boarding School is one of the biggest pesantren in East Java which teaches both religion and academic subjects for the same 100%. One of subjects taught is Tarjamah which serves as a very important subject. As an attempt to make it easier for teachers to teach the subject as well as for students not to be bored in the teaching and learning activity, it is essential for the teachers to choose and implement a suitable teaching strategy. One of the suitable strategies in Tarjamah subject is Jigsaw. This study aims at (1) describing teaching steps in Tarjamah subject using Jigsaw strategy (2) knowing the improvement of students’ active participation using Jigsaw teaching strategy.This study is a Classroom Action Research (CAR), that is, a study which is implemented by a teacher in his own classroom using qualitative research design. This study consists of 2 cycles and each cycle consists of 4 steps which are: designing, implementing, observing, and reflecting. Data collection techniques which are used are: (1)observation on students’ active participation, (2)interview, (3)documentation, in which the data is analyzed using Miles and Huberman theory covering 3 steps which are: Data reduction, Data presentation, and Conclusion.From the data analysis, it is shown that (1) there are 7 steps in implementing Jigsaw strategy in Tarjamah subject which are: the teacher entered the classroom by saying salam, the teacher explained the materials which will be learnt, the students were divided into one group, students sat on their group, the students were given materials by the teacher, each group discussed the materials, after the students were finished discussing, they formed new groups to present the materials they had learnt, the teacher gave evaluation on students’ presentation. (2) the implementation of Jigsaw strategy in Tarjamah subject can improve students’ active participation in learning which can be seen from the conducive learning atmosphere during the teaching and learning activity as well as the students’ opinion who expressed their happiness and enthusiasm on the implementation of this strategy.Keywords: Jigsaw strategy, teaching and learning activity, translation, santriwati, teacher, semester, teaching curriculum. تنفيذ إستراتبجبة جكسو (Jigsaw) لترقية نشاط الطالبات في تعلم مادة الترجمة للفصل الرابع F بكلية المعلمات الإسلامية معهد دارالسلام كونتور للبنات الحرم الثالث العام الدراسي 1438-1439 هلطفى محيى الدين، حضرتي ضرفىluthfimuhyiddin@unida.gontor.ac.id, hazratizharfa@gmail.comجامعة دار السلامملخصالمعهد دار السلام كونتور من أكبر المعهد الإسلامي في جاوى الشرقية الذي تعلم مائة من مائة العلوم الدينية ومائة من مائة العلوم الكونية. ومن إحدى الدروس التي تعلّم في معهد دارالسلام للتربية الإسلامية الخديثة كونتور هي الترجمة، أهم الدرس للغة.ولتكون المعلمة ناحة في تعليمها ولا تشعر المتعلم متسائمة في عملية التعليم والتعلم فلا بد لها المهارة في اختيار وتنفيذ إستراتيجية التعلم. وإحدى من الإستراتيجية المناسبة وهي إستراتيجية جكسو. الهدف من هذا البحث للكشف عن (1) خطوات التدريس بالإستراتيجية جكسو في مادة الترجمة (2) فعالية ترقية نشاط الطالبات بتنفيذ إستراتيجية التعلم جكسو. يستخدم هذا البحث عملية البحث في الفصل الدراسي (CAR) وهي البحث الذي عقدته المعلمة في فصلها، وكانت عملية البحث في الفصل الدراسي من الدراسة الكيفية. ويتكون هذا البحث من الدورين وفي كل دور يشمل على أربع مواحل وهي: التخطيط، التنفيذ، الملاحظة، والمنعكسة. والمناهج المستخدمة لجمع البيانات هي: (1) المنهج الملاحظة الاشتراكية عن نشاط الطالبات (2) منهج المقابلة (3) منهج الوسائق المكتوبة. وتحليل البيانات من المنهج مليس وهوبيرمان (Miles and Huberman) الذي يحتوي على ثلاث خطوات، وهي: (1) تخفيض البيانات (2) عرض البيانات (3) الاستنتاج و التحقيق. ونتيجة البحث من هذا البحث (1) كان التعليم الترجمة بتنفيذ إستراتيجية جكسو (Jigsaw) تحتوي على سبعة خطوات وهي: دخلت المدرسة الفصل بإلقاء السلام ثم المقدمة، شرحت المدرسة المادة التي عينت نقلها، قسمت المدرسة إلى خمسة فروق ولكل فرقة تتكون على ثماني طالبات، أمرت المدرسة الطالبات للجلوس حسب الفرقة، أعطت المدرسة المادة إلى كل فرقة ليناقشن، ولكل نفر تكون فريق الخبراء، فبعد المناقشة، أمرت المدرسة الطالبات ليجتمعن بفرقة أخرى لتلقي ما نقشت، ألقت المدرسة التقييمات عن المادة التي نقشت.(2) كان تنفيذ إستراتيجية جكسو (Jigsaw) ترقي نشاط الطالبات عند التعلم.الكلمات الرئيسية: أستراتيجة جكسو، التعليم، الترجمة، الطالبات، المدرّسة، الفصل الدارسي، المنهج التعليمي.